Supressão viral do HIV nos 12 primeiros meses de terapia antirretroviral: análise comparativa de esquemas estruturados com dolutegravir ou efavirenz, Minas Gerais 2015-2017 - Gabriella Jomara da Silva (2020)
Background: Changes in guidelines for peoples living with HIV (PLHIV) in recent years require an assessment of the first-line antiretroviral therapy (ART) effectiveness in the real-world scenario. Objective: to evaluate the viral suppression in the first year of antiretroviral treatment with dolutegravir (DTG) vs. efavirenz (EFV), and verify associated factors. Methods: This was a historical cohort study with PLHIV ≥18 years old, who started ART between 2015 and 2017 in Minas Gerais state (n=2.599). Information about age, gender, residence, viral load (VL), CD4⁺ cell count and antiretroviral dispensing were extracted from two Unified Health System databases. Viral suppression (VL <50 copies/mL) was analyzed in intention-to-treat (ITT) compared with per-protocol analysis and with VL <1.000 copies/mL. The time until the first recorded of VL <50 copies/mL was estimated by the Kaplan-Meier method. Cox proportional hazards model (HR) to determine predictors of viral suppression after six months initiating ART. Logistic regressions were used to estimate adjusted odds ratios (aORs) in the first 12 months of treatment. Statistical significance was defined a level of 5% and 95% confidence interval (95%CI). Results: Selected 2.599 individuals, 34% starting treatment with DTG and 66% with EFV. There was a predominance of men (77.5%), median age of 34 years old, baseline CD4⁺ 322 cell/mmᵌ and VL 4.7 (log) copies/mL. The changes in the ART occurred in 5% of PLHIV that began with DTG and 9.2% with EFV-based regimens (p<.0001). In ITT, higher proportion of viral suppression was observed for DTG compared to EFV (76.7% vs. 58.1%), even considering VL <1.000 copies (p<0.0001). DTG-based regime had less time until the first recorded of VL <50 copies/mL after six months initiating ART (HR=1.29; 95%CI 1.15 – 1.43) and higher odds in the first 12 months (aORs=2.44; 95%CI 2.01 – 2.95). ART initiation <120 days, CD4⁺ T-cell count ≥200 cell/μl and baseline VL <100,000 copies/mL also had higher odds of viral suppression. In protocol analysis was observed largest proportion of viral suppression and ART groups had the same time interval until the outcome. Conclusion: After the introduction of DTG, the viral suppression results were improved, though observed proportions was lower than the expected according to the third global target.